Modern Luminescence Spectroscopy of Minerals and Materials - Gaft, Michael; Reisfeld, Renata; Panczer, Gerard (Springer Mineralogy, 2015)
The book is devoted to three types of laser-based spectroscopy of minerals, namely Laser-Induced Time-Resolved Luminescence, Laser-Induced Breakdown spectroscopy and Gated Raman Spectroscopy. This new edition presents the main new data, which have been received after the publication of the first edition ten years ago both by the authors and by other researchers. During this time, only the authors published more than 50 original papers devoted to laser-based spectroscopy of minerals. A lot of new data have been accumulated, both in fundamental and applied aspects, which are presented in new edition.